The Effect of Chinese Herbal Medicine Combined With Western Medicine on Vascular Endothelial Function in Patients With Hypertension: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Ren, Weiquan; Wang, Miyuan; Liao, Jiangquan; Li, Lingling; Yang, Deshuang; Yao, Ruiqi; Huang, Li (Frontiers in Pharmacology, 2020)
Objective Vascular endothelium plays a fundamental role in regulating endothelial dysfunction, resulting in structural changes that may lead to adverse outcomes of hypertension. The aim of this study was to systematically evaluate the effect of a combination of Chinese herbal medicine (CHM) and Western medicine on vascular endothelial function in patients with hypertension. Methods We systematically searched the literature for studies published in Chinese and English in PubMed, Embase, Cochrane Central Register of Controlled Trials, Chinese Biomedical Literature Database, China Knowledge Resource Integrated Database, Wanfang Data, and China Science and Technology Journal Database. Databases were searched using terms concerning or describing CHM, hypertension, vascular endothelium, and randomized controlled trials. RevMan 5.3.0 was used for data analysis. If the included studies were sufficiently homogeneous, quantitative synthesis was performed; if studies with different sample sizes and blind methods were used, subgroup analyses were performed. GRADEpro was selected to grade the current evidence to reduce bias in our findings. Results In this review, 30 studies with 3,235 patients were enrolled. A relatively high selection and a performance bias were noted by risk of bias assessments. Meta-analysis showed that the combination of CHM and conventional Western medicine was more efficient than conventional Western medicine alone in lowering blood pressure (risk ratio, 1.21; 95% CI, 1.16 to 1.26) and increasing nitric oxide (95% CI, 1.24 to 2.08; P < 0.00001), endothelin-1 (95% CI, −1.71 to −1.14; P < 0.00001), and flow-mediated dilation (95% CI, 0.98 to 1.31; P <0.00001). No significant difference was observed between the combination of CHM and conventional Western medicine and conventional Western medicine alone for major cardiovascular and cerebrovascular events. CHM qualified for the treatment of hypertension. The GRADEpro presented with low quality of evidence for the available data. Conclusion CHM combined with conventional Western medicine may be effective in lowering blood pressure and improving vascular endothelial function in patients with hypertension. To further confirm this, more well-designed studies with large sample sizes, strict randomization, and clear descriptions about detection and reporting processes are warranted.